CHANGE OF HYPERTENSION TREATMENT SCHEME IN OUTPATIENT CARE AT SPECIALIZED CARDIOLOGIC INSTITUTION, AND FACTORS ASSOCIATED WITH THE CHANGE OF ANTIHYPERTENSION THERAPY - A. V. Kontsevaya; T. S. Romanenko; V. A. Vygodin; S. B. Fitilev (Российский кардиологический журнал, 2015)
Compliance to the recommended treatment strategy is a significant component ofadherence to antihypertension therapy (AT) that is associated with treatmentefficacy and economical benefits.Aim. To study the scheme of drug therapy in patients with arterial hypertension (AH),first time requested cardiological assessment, during 6 month since the moment ofthe admittance with the assessment of factors associated with the treatmentscheme.Material and methods. The study done in 2 stages. First stage was focused onthe selection of patients who first time presented at one of the districtcardiodispensaries in Moscow (CD) among those with AH, from January toDecember. The expert charts were completed according to the source documents(n=1766). Second stage was focused on the phone survey in 6 months afterprimary admittance (n=1419).Results. Analysis of AT compliance showed that the patients in specializedcardiological institution have low level of adherence to physicians' recommendationson the treatment scheme; in 6 months only 25,1% continued taking recommendeddrugs. More than a half (52,4%) of those who changed treatment scheme, done inon their own, without physician assessment. One of the reasons was distrust to physician's recommendations (48,6%). Probability of the change of cardiologist-recommended AT was significantly related to the factors as an opportunity to get the drugs by discount rate (as incentives) (OR 2,4), coronary heart disease (OR 2,0), hypertension for less than 5 years (OR 1,5), hypertensive crises (OR 1,9), intake of three and more cardiovascular drugs (OR 2,4) and the absence of drug combinations in the scheme (OR 1,4).Conclusion. Patients of the specialized cardiological institution have low level of physician recommendations adherence by the 6-month scheme of treatment, they correct their treatment themselves, and the motivation for the scheme change their name distrust to the treating physician.